2021
DOI: 10.3390/jcm10245876
|View full text |Cite
|
Sign up to set email alerts
|

Autopsy Findings and Causality Relationship between Death and COVID-19 Vaccination: A Systematic Review

Abstract: The current challenge worldwide is the administration of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccine. Considering that the COVID-19 vaccination represents the best possibility to resolve this pandemic, this systematic review aims to clarify the major aspects of fatal adverse effects related to COVID-19 vaccines, with the goal of advancing our knowledge, supporting decisions, or suggesting changes in policies at local, regional, and global levels. Moreover, this review aims to provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 44 publications
1
43
0
2
Order By: Relevance
“…However, following some severe adverse events, a growing lack of confidence developed in many European countries, slowing down the worldwide vaccination program [ 98 , 99 ]. Similar to the case of the definition of the main pathophysiological aspects of the SARS-CoV-2 infection, post-mortem investigations have been instrumental in identifying the cause of death in fatal cases following vaccine administration [ 100 , 101 , 102 , 103 ]. Autopsy has also become crucial in establishing the causality relationship between vaccine administration and fatal adverse events [ 104 ].…”
Section: The Scovid-19 Pandemic and Its Impact On Forensic Investigat...mentioning
confidence: 99%
“…However, following some severe adverse events, a growing lack of confidence developed in many European countries, slowing down the worldwide vaccination program [ 98 , 99 ]. Similar to the case of the definition of the main pathophysiological aspects of the SARS-CoV-2 infection, post-mortem investigations have been instrumental in identifying the cause of death in fatal cases following vaccine administration [ 100 , 101 , 102 , 103 ]. Autopsy has also become crucial in establishing the causality relationship between vaccine administration and fatal adverse events [ 104 ].…”
Section: The Scovid-19 Pandemic and Its Impact On Forensic Investigat...mentioning
confidence: 99%
“…Finally, vaccination could also be a useful tool to prevent the spread of COVID-19 infection in prisons. In fact, to date, vaccination is the most effective means of prevention and treatment against COVID-19, reducing incidence, morbidity, hospitalization, and mortality [ 12 , 13 , 14 , 15 , 16 ]. However, studies on the effectiveness of the vaccination campaign in prisons are few and hopefully will be implemented in the future.…”
Section: Introductionmentioning
confidence: 99%
“…In these countries, vaccine acceptance was positively associated with COVID-19 knowledge and threat regarding COVID-19. However, as information that COVID-19 vaccine-induced death spread within communities [ 38 ], a study indicated a low-risk perception of COVID-19 among Sub-Sahara Africans [ 39 ]. Therefore, fear of adverse effects from vaccines “makes sense”.…”
Section: Discussionmentioning
confidence: 99%